Massive normalization of olfactory bulb output in mice with a 'monoclonal nose' - Roland, Benjamin; Jordan, Rebecca; Sosulski, Dara L; Diodato, Assunta; Fukunaga, Izumi; Wickersham, Ian; Franks, Kevin M; Schaefer, Andreas T.; Fleischmann, Alexander (eLife, 2016)
Perturbations in neural circuits can provide mechanistic understanding of the neural correlates of behavior. In M71 transgenic mice with a “monoclonal nose”, glomerular input patterns in the olfactory bulb are massively perturbed and olfactory behaviors are altered. To gain insights into how olfactory circuits can process such degraded inputs we characterized odor-evoked responses of olfactory bulb mitral cells and interneurons. Surprisingly, calcium imaging experiments reveal that mitral cell responses in M71 transgenic mice are largely normal, highlighting a remarkable capacity of olfactory circuits to normalize sensory input. In vivo whole cell recordings suggest that feedforward inhibition from olfactory bulb periglomerular cells can mediate this signal normalization. Together, our results identify inhibitory circuits in the olfactory bulb as a mechanistic basis for many of the behavioral phenotypes of mice with a “monoclonal nose” and highlight how substantially degraded odor input can be transformed to yield meaningful olfactory bulb output.